A conciliação judicial trabalhista : possibilidade de otimização a partir da aplicação de técnicas e ferramentas inerentes aos mecanismos negocial e mediativo de solução de conflitos : volume 1, 2 e 3 - Campos, Amália Rosa de (2021)
Labor judicial conciliation, despite its inquestionable relevancy to labor procedure, is a scarcely addressed theme by specialized literature, that does not usually deal with issues such as the structure and set of tools that should be used by magistrate judges to seek agreements. Adhering to the concentration área of “Theoiry of Jurisdiction and Process” and to the line of research “Jurisdiction, Efectiveness and Procedural Instrumantality”, the study aims to determine whether – and to what extent – it’s possible to apply negotiation and mediation techniques of conflict resolution to judicial conciliation attempts, in order to fill this hiatus. Adopting a hypothetical-deductive approach method, typological, functionalist, historical-comparative and monographic procedure methods, as well as a systematic interpretation method, the study revolves around a central issue related to the possibility of adapting the procedures inherent to interest-based negotiation and traditional mediation in order to provide a minimal and flexible structure to judicial conciliation is approached. Therefore, among others, the possibility of usage by the magistrate of the annexed duties of the cooperative model of procedural organization to seek for agreements is maintained; it is established that access to justice needs to be reframed so that appropriate methods of conflict resolution are considered as instruments of jurisdictional provision in a broad sense; through field research, self-composing mechanisms offered by the labor Multidoor Courthouse system are mapped and quantifyed, confirming the relevant role played by judicial conciliation in this context; and the stages and communicational techniques inherent to negotiation and mediation mechanisms appliable to judicial conciliations are analyzed. Based on the empirical-theoretical path taken, it’s concluded that the methodological exchange between self-composing conflict resolution mechanisms is not only possible, but effectively recommendable, as it allows: from a juridical stance, a standardization and perfectibilization of the judicial conciliation procedure and the reduction of the negative externalities linked to self-composition attempts made by judges; and form a social point of view, the education and incentive for disputants to autonomously solve conflicts and to combat, in the long run, the conflict and litigation cultures.